2018
DOI: 10.22214/ijraset.2018.1228
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of MSE Wall with different Soil Properties and Reinforcement Length

Abstract: The Mechanically Stabilised Earth (MSE) retaining wall is used as an alternative designed structure for conventional cast-in-place concrete type walls and gravity walls. The MSE wall behaves as a coherent block considered as flexible, which can sustain loading types and deformations due to the interaction between the backfill and the inclusion materials. The construction of MSE walls is cost effective, requires less site preparation, and is technically more feasible. MSE wall behaviour highly depends upon type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…FLAC, MSEW, ReSSA and PLAXIS are such popular computer programs which can be used for numerical simulation and analysis of MSE walls. Many parametric studies using such programs were also carried to get insights into the design and behaviour of MSE walls with different geometries, materials and loading conditions [13][14][15][16][17][18][19][20]. In a study conducted by Kenneth et al [19], PLAXIS, a finite element programme, and UTEXAS4, a limit equilibrium programme, were used to examine stresses and stability of MSE retaining walls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…FLAC, MSEW, ReSSA and PLAXIS are such popular computer programs which can be used for numerical simulation and analysis of MSE walls. Many parametric studies using such programs were also carried to get insights into the design and behaviour of MSE walls with different geometries, materials and loading conditions [13][14][15][16][17][18][19][20]. In a study conducted by Kenneth et al [19], PLAXIS, a finite element programme, and UTEXAS4, a limit equilibrium programme, were used to examine stresses and stability of MSE retaining walls.…”
Section: Introductionmentioning
confidence: 99%
“…On weak foundation soil weak backfill soil is more suitable, on medium foundation soil medium backfill soil is more suitable and on good foundation soil good backfill soil is more suitable. Using the finite element numerical programme PLAXIS 2D, Hulagabali et al [15] analysed the impact of backfill and reinforcement on the behaviour of MSE walls. Soil parameters, including friction angle and retained and foundation soil unit weight, were studied to determine their effects on wall deformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors can influence the MSE wall performance and deformation behavior . A. Hulagabali et al [4], found that as the unit weight of retained soil increases, there was increase in wall deformations, and as the friction angle of the reinforced and foundation soil increased, wall deformations were reduced with increase in reinforcement length. Also, reinforcement stiffness and length were identified as influential parameters affecting the horizontal movement at a specific MSE wall height.…”
Section: Introductionmentioning
confidence: 99%